Sosialisasi Perbankan Syariah Ditengah Pandemi Covid-19 Di Masjid Nuruddin Desa Gelebak Dalam Kecamatan Rambutan Kabupaten Banyuasin Palembang - Choiriyah Choiriyah (AKM, 2021)
This community service activity discussed the introduction of Islamic Banking in the midst of the Covid-19 pandemic at the Nuruddin Mosque, Gelebak Dalam Village, Rambutan District, Banyuasin Regency, Palembang. The purpose of this community service activity is to provide an introduction to Sharia Banking to the people of Gelebak Dalam Village with the hope that the community or socialization participants can understand the current existence of Islamic banking which is everywhere both in villages and in urban areas. The socialization participants can also find out that sharia talks are currently being discussed by many people. Sharia banking is a banking system developed based on sharia or Islamic law.